PENGARUH LITERASI KEUANGAN TERHADAP PEMBELIAN IMPULSIF PADA PRODUK FASHION - Shafira Anggun Aulia; Nathashia, Kyara; Kurniawati, Meike (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
The continuously evolving fashion trends, which show no signs of slowing down, have negative impacts on both individuals and the environment. This phenomenon also drives consumers to constantly follow trends without proper financial planning, leading to impulsive buying behavior. This study aims to identify the influence of financial literacy on impulsive buying of fashion products. The data in this research were obtained using a quantitative approach, with participants aged 18–25 years, representing various genders, locations, and monthly expenditure levels, and having prior experience with impulsive purchases of fashion products in the recent past. Data were collected through a questionnaire distributed via Google Forms, resulting in a total of 86 respondents. The data were analysed with simple regression and processed using SPSS 26. The study found that financial literacy has a significant negative effect on impulsive buying behavior, particularly among Gen Z consumers in the context of fashion products.